The Effect of Guano Walet Fertilizer and Ratu Biogen Foliar Fertilizer on the Growth and Yield of Tomato (Lycopercicum esculentum Mill.) Monza Variety - Dian Kristina; Abdul Rahmi (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
This experiment aims to: (1) to study of the effect of guano walet fertilizer and Ratu Biogen foliar fertilizeras well as their interaction on the growth and yield of tomato plants; and (2) to find proper dosage of guano walet fertilizer and proper concentration of Ratu Biogen foliar fertilizer for better growth and yield of tomato plants.The research carried out from May 2014 to July 2014, in the Village Melak Ulu RT.20 Subdistrict Melak, West Kutai. It applied Completely Randomized Design with factorial experiment 4 x 4 and five replications.  The first factor is the dosage of the guano walet fertilizer (G) consists of 4 levels, namely: no fertilizer application guano walet (g0), 10 Mg ha ̵ ¹, or 100 g of polybag ̵ ¹ (g1), 15 Mg ha ̵ ¹ or 150 g polibag ̵ ¹ (g2), 20 Mg ha ̵ ¹ or 200 g polybag ̵ ¹   (g3). The second factor is the concentration of Ratu Biogen (B) consists of 4 levels: without POC Ratu Biogen (b0), 1 ml 1 ̵ ¹ water (b1), 2 ml 1 ̵ ¹ water (b2), 3 ml 1 ̵ ¹  water (b3).Result of the research revealed that : (1) application of guano walet fertilizer affect very significantly on plant height at 14, 28, 42 days after planting, the number of fruits per plant, and weight of fruit per plant, but the effect is not significant on the days of plant flowered and days of plant harvest.  The best production is attained by the 200 g polybag-1 fertilizer guano walet (g3), namely 282,50 plant-1, In reverse, the least production is attained by without fertilizer guano walet (g0), namely 227,25 g plant ̵ ¹; (2) application of Ratu Biogen foliar fertilizer after significantly to very significantly on the plant height at 14 days after planting  and the number of fruits per plant, but the effect is no significant on the plant height at 28 and 42 days after planting, days of plant flowered, days of plant harvest, and weight of fruit per plant; and (3) interaction between guano walet fertilizer and Ratu Biogen foliar fertilizer no significantly on the plant height at 14, 28, and 42 days after planting, days of plant flowered, days of plant harvest, number of fruit per plant, and fruit weight per plant.